2004
DOI: 10.1021/ma035768t
|View full text |Cite
|
Sign up to set email alerts
|

“Controlled” High-Speed Anionic Polymerization of Propylene Oxide Initiated by Alkali Metal Alkoxide/Trialkylaluminum Systems

Abstract: The anionic polymerization of propylene oxide initiated by alkali metal alkoxide suffers from several drawbacks such as a slow polymerization rate in nonpolar solvents and an important chain transfer reaction to monomer. We found that the addition of trialkylaluminum to the alkali metal alkoxide/ propylene oxide system in hydrocarbon media strongly enhances the polymerization rate and strongly reduces the transfer reactions, thus allowing the controlled synthesis of poly(propylene oxide) with relatively high m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(180 citation statements)
references
References 14 publications
9
166
0
5
Order By: Relevance
“…and P2 0 could also be assigned to PPO chains with allyloxy and hydroxide end groups [13,14,42] or even to PPO chains with isobutyl and hydroxide end groups [43,44]. However, looking at the allylic and aliphatic regions of NMR spectra of those polymers, no peak characteristic of respectively transfer to monomer or isobutyl initiation is observed, as also shown in another work [33].…”
Section: Resultssupporting
confidence: 55%
“…and P2 0 could also be assigned to PPO chains with allyloxy and hydroxide end groups [13,14,42] or even to PPO chains with isobutyl and hydroxide end groups [43,44]. However, looking at the allylic and aliphatic regions of NMR spectra of those polymers, no peak characteristic of respectively transfer to monomer or isobutyl initiation is observed, as also shown in another work [33].…”
Section: Resultssupporting
confidence: 55%
“…[30,32] Although it cannot be precisely quantified the amount of H-PEEGE-OH chains resulting from this side initiation process appears almost negligible as compared to the azido-functionalized ones.…”
Section: Copolymerization Studiesmentioning
confidence: 99%
“…In recent works we have found that very simple initiators based on the association of alkali metal derivatives [4,5] or tetralkylammonium or tetraalkylphosphonium salts [6] with triisobutylaluminum (i-Bu 3 Al) yield a rapid and controlled polymerization of propylene oxide whereas transfer to monomer was strongly reduced or even suppressed. As it may be seen in Table 1 In contrast, in the presence of an excess of the aluminic compound, polymerization proceeds rapidly, up to complete monomer conversion.…”
Section: Propylene Oxide Activated Anionic Polymerizationmentioning
confidence: 99%
“…As it may be seen in Table 1 In contrast, in the presence of an excess of the aluminic compound, polymerization proceeds rapidly, up to complete monomer conversion. In the temperature 4 Cl salts , whereas for a given counterion the polymerization rate directly increases with the amount of trialkylaluminum which acts as an activator/catalyst for the polymerization. Since when initiators are used alone or at ratio initiator/i-Bu 3 Al of 1:1, no polymerization proceeds, these results sustain the selective insertion of a i-Bu 3 Al complexed monomer which is electrophilically activated.…”
Section: Propylene Oxide Activated Anionic Polymerizationmentioning
confidence: 99%